2014
DOI: 10.4269/ajtmh.13-0697
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia africae and Candidatus Rickettsia barbariae in Ticks in Israel

Abstract: Abstract. DNA of several spotted fever group rickettsiae was found in ticks in Israel. The findings include evidence for the existence of Rickettsia africae and Candidatus Rickettsia barbariae in ticks in Israel. The DNA of R. africae was detected in a Hyalomma detritum tick from a wild boar and DNA of C. Rickettsia barbariae was detected in Rhipicephalus turanicus and Rhipicephalus sanguineus collected from vegetation. The DNA of Rickettsia massiliae was found in Rh. sanguineus and Haemaphysalis erinacei, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…Rickettsia africae was detected in a few local ticks from northern Israel. Previous studies showed R. africae in Hyalomma ticks collected in southern Israel, and the authors hypothesized that it was imported to Israel from tick-infested camels arriving from Egypt (20,22). Thus, our findings may indicate that R. africae propagated since its original introduction to the country via Hyalomma ticks.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Rickettsia africae was detected in a few local ticks from northern Israel. Previous studies showed R. africae in Hyalomma ticks collected in southern Israel, and the authors hypothesized that it was imported to Israel from tick-infested camels arriving from Egypt (20,22). Thus, our findings may indicate that R. africae propagated since its original introduction to the country via Hyalomma ticks.…”
Section: Discussionsupporting
confidence: 48%
“…Israel is a region endemic for Israeli spotted fever caused by Rickettsia conorii israelensis, where fatal cases have been reported (18,19). SFGR, such as R. felis, R. sibirica mongolitimonae, R. africae, R. massiliae, and R. aeschlimannii, were also found in various tick species in Israel, including in Hyalomma species (20)(21)(22). However, the distribution of the SFGR species among the various Hyalomma species and those introduced to Israel was never investigated.…”
mentioning
confidence: 99%
“…Bats, birds and reptiles are considered as accidental hosts [4–6]. This species is also known to feed on humans in the adult stage [7], and is a potential vector of zoonotic rickettsiae ( Rickettsia massiliae [8], R. raoultii [9] and R. heilongjiangensis [10]).
Fig. 1Distribution map of the three subspecies of Haemaphysalis erinacei based on literature data, and including geographical locations of the specimens collected in the present study ( yellow crosses )
…”
Section: Introductionmentioning
confidence: 99%
“…19 It has been detected also in other countries, like Cyprus, Israel and Portugal (PoTiRb169). [25][26][27] Additional Candidatus Rickettsia spp. have been described in Europe in the last 10 years, and their role for humans remains to be elucidated.…”
Section: Transactions Of the Royal Society Of Tropical Medicine And Hmentioning
confidence: 99%